Crenças e percepções frente ao aborto: uma visão masculina - Gusmão , Cleonides Silva Dias (2016)
The male experiences relating to abortion are not covered. One of the fields where the social debate about abortion is structured is the field of gender relations, indicating as exclusively female issue. How pregnancy occurs in a woman's body, man becomes just a companion. The particularities of men and women, following this reasoning, are perceived as inherent to each of them, therefore, essentialist, rigid, unchanging character. Part, therefore, the assumption that the explanations in social beliefs on abortion are based on two lines of opposite thoughts - essentialism and constructivism. Whereas the influence of perceptions and social beliefs about abortion may increase the understanding of the different ways of approaching the subject, the objective of this study lies in the analysis of beliefs and perceptions of men who shared the experience of abortion - spontaneous or induced - with some partner. Sample: The sample, characterized as non-probabilistic convenience, consisted of 20 men over the age of 18 who shared an abortion experience with your partner, whether spontaneous or induced, located through technical Snowball. The number of participants was determined by the saturation criterion. Instruments: demographic questionnaire, with the variables of interest to age, race, occupation, income, education, place of residence, religion, religion, marital status, number of children, relationship where abortion occurred. Semistructured interview that aims to evoke, enunciation and investigation on the issues of abortion. Procedures: After approval by the Ethics Committee, the application of the instruments was started. On being contacted, participants are informed about the study, explaining the voluntary nature of their participation, followed by the signing of free and informed consent. The interviews were recorded, with the permission of respondents, for later transcription and analysis. Data Analysis: The data relating to sociodemographic questionnaire were analyzed using descriptive statistics in order to build a profile of the sample. Interviews after transcribed, were analyzed on the basis of certain categories from the raised issues, being processed in two stages, as proposed by Figueiredo (1993). Results: Two thematic classes were identified from the analysis, namely: Experiences male reproductive process and male reproductive process Perception. The first thematic class is characterized by the description of the abortion happened to each of the respondents, the feelings evoked this event as well as other categories that are geared to the experiences of men in relation to the reproductive process, such as pregnancy, caring for children, birth and parenthood. Thus, this thematic class rescues the experiences evoked by men as well as fruit feelings of such experiences. The second thematic class concerns how respondents sighted abortion, being permeated by social beliefs, especially essentialist beliefs of gender and religious beliefs; revealing thus their perception of miscarriage, abortion and compared their experiences. Final Considerations: Through analysis can be seen that the behavior of men do not differ from their perceptions and beliefs, so that essentialist gender and religious beliefs guide behavior (notable through the first thematic class) and perceptions (notable through the second thematic class ) of respondents about contraception, pregnancy, abortion, and caring for children. Such beliefs are passed on to future generations, which contiuam to build on and strengthen a society based on desigualdes and gender differences.